Geriatric Depression and Its Association with Geriatric Malnutrition: A Cross-Sectional Study in Hubballi, North Karnataka - Nekar, Manjunath S; Joshi, Anjana R; Bant, Dattatraya D (National Journal of Community Medicine, 2022)
Background: The world's elderly population is increasing rapidly. According to the 2011 census elderly population contributes to 7.4% of the total population. Both physical and mental disorders are prevalent among the elderly. Symptoms of depression in older people are often overlooked and untreated. Depression leads to loss of appetite, diminution of food intake, and weight loss consequently leading to malnutrition. Methodology: A community-based cross-sectional study was conducted among the geriatric population of urban field practice area using a predesigned, semi-structured questionnaire. Geriatric Depression was assessed using Geriatric Depression Scale and Nutritional Status using the Mini Nutritional Assessment Scale. House to house survey of the Geriatric population was conducted after obtaining written consent. Results: Out of 260 participants, 51.5% of the population were males, 49.2% of the population belonged to 60-69 years age group and 16.9% of them were more than 80 years of age. The prevalence of geriatric depression was 68.5 %,). The majority (64%) of the elderly population were at risk of malnutrition. Depression scores were negatively correlated with nutritional scores. Conclusion: The prevalence of depression and malnutrition was considerably high among the elderly population. Malnutrition among the elderly is a significant determinant of malnutrition.